Eye injury treatment in intensive care unit patients - L. K. Moshetova; S. A. Kochergin; A. S. Kochergin (Oftalʹmologiâ, 2015)
Aim. To describe eye injuries in intensive care unit (ICU) patients with multitrauma, to study conjunctival microflora in these patients, and to develop etiologically and pathogenically targeted treatment and prevention of wound complications.Materials and methods. Study group included 50 patients (54 eyes) with combined mechanical cerebral and eye injury. All patients underwent possible ophthalmological examination (biomicroscopy, ophthalmoscopy and ocular fundus photographing with portative fundus camera, tonometry), cranial CT and MRT, and bacteriological study of conjunctival smears. Results. Modern methods of ophthalmological examination of ICU patients provided correct diagnosis and prediction of wound healing. Eye injury treatment schedule provided maximum possible results in all ICU patients. Hospitalacquired infection results in asymptomatic dissemination of pathogenic microbes on ocular surface. Conclusions. 14-day topical treatment with antimicrobials, steroids, and NSAIDs reduces posttraumatic inflammation caused by mechanical eye injuries in ICU patients. Bacteriological studies of conjunctival smears demonstrate the presence of pathogenic flora in ICU patients. In these patients, the most effective antibacterial agents are third-generation fluoroquinolones.